THE EFFECT OF USING BALL TOSS STRATEGY IN TEACHING VOCABULARY AT THE FOURTH GRADE OF SDN 023 PANDAU JAYA - Sudarmiati Sudarmiati (English Language Education and Current Trends (ELECT), 2022)
The purpose of this research was to find out there was significant effect of the students who were taught by using ball toss strategy better than the students who were not taught on vocabulary mastery at the fourth grade of SDN 023 Pandau Jaya. This research was Quasi Experimental research. The population of this research was the the fourth grade of SDN 023 Pandau Jaya. The number of sample was 56 students; Experimental class was IV.A consisting of 28 students, and Control class was IV.C consisting of 28 students. After calculating U-Mann whitney test, the researcher found that Asymp.Sig 2 tailed < Significant level (0.00 < 0.05), so that Alternative Hypothesis was accepted, it meant that there was significant effect of using Ball Toss Strategy toward students’ vocabulary mastery at the fourth grade of SDN 023 Pandau Jaya and the average post-test score of experimental class was 71.42, increased from pre-test score 54.10. The average post-test on control class was 63.57 was lower than Experimental class. N-Gain of this research was 0.35, it was categorized middle. As the conclusion, there was different vocabulary mastery of the students who received in class instruction of ball toss strategy than students who did not receive instruction of ball toss strategy.   REFERENCES Aefsky, Fern. 2000. Making decision about diverse learners. United States. Handbooks, manuals. Allen, Janet. 1999. Word and Word in teaching Vocabulary in Grade 4-12. Portland: Stelhouse Publishers. Alicia.  2010. Teaching Vocabulary by Using Ball Toss Review Strategy at Elementary School 144 Padang. Retrieved on April 2014. http://ejournal-s1.stkip-pgri-sumbar.ac.id/index.php/Inggris/article/view/737/728 Asfiyah. 2011. The Use of Ball Toss Strategy to Improve Students Vocabulary in Concrete Noun (An Experimental Research at the Second Grade of MTS. Mafatihut Thullab An-Nawawy Surodadi Jepara in Academic Year of 2010/2011. Retrieved on April 2014. Unpublished Thesis: http://library. walisongo.ac.id/digilib/files/disk1/115/jtptiain-gdl-asfiyah-5707-1-053411341.pdf Creswell, Jhon W, 2005. Educational Research Planning, Conducting, and Evaluating Quantitative and Qualitative Research. Second Edition. USA: University of Nebraska-Linclon. Eckersley, C.E. 1960. A Comprehensive English Grammar for Foreign Language Students. London: Longman. Hasanah. 2013. Teaching English Vocabulary Using Ball Toss Strategy at the Fourth Grade Students of SDN Cibeber Mandiri 1 Cimahi in Academic Year 2012-2013.Retrieved on April 2014. Unpublished thesis: http://publikasi.stkipsiliwangi.ac.id/wp-content/blogs.dir/2 /files/ 2013/11 /0922055567-Hasanah. Hornby, AS.2000. Oxford Advanced Learner’s Dictionary. Oxford university Press. Khaty. 2010. 40 active strategy learningstrategies inclusive Classroom. United States. Lybrary of congres catalog. Leaver,et al.2005. Achieving Success in Second Language Acquisition. Cambridge  University Press. Linse, Caroline. 2006. Practical English Language Teaching: Young Learners. NewYork: McGraw Hill. Meltzer,D.E. 2002. The relationship between Mathematics Preparation and Conceptual Learning Gains in Physic: A possible: “hidden variable” in diagnostic pretest score. American Journal. Nunan, David. 1991. Practical English Language. America: Cambridge University Press. Septiani. 2013. Teaching Vocabulary Using Ball Toss Strategy on Students of Elementary (A Case Study at the Sixth Grade SD Pandu Bandung. Retrieved on April 2014. Unpublished thesis: http://publikasi.stkipsiliwangi.ac.id/wp-content/blogs.dir/2/files/2013/11/09220536-Septiani. Sugiyono, Prof.Dr. 2010. Statiska Untuk Penelitian. Bandung. CV.Alfabeta Toby. 2002. Strategies for teaching. San Francisco: Market Strevrt. Ur, Penny. 1991. A Course in Language Teaching: Practiceand Theory. Cambridge University Press. Zulkarnain. 2010. Statiska Penelitian. Pekanbaru: Cendekia Insani Pekanbaru.